2015
DOI: 10.4085/1062-6050-49.3.72
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Eccentric Strength of the Shoulder External Rotators Using a Handheld Dynamometer: Reliability and Validity

Abstract: Context: Shoulder strength assessment plays an important role in the clinical examination of the shoulder region. Eccentric strength measurements are of special importance in guiding the clinician in injury prevention or return-to-play decisions after injury.Objective: To examine the absolute and relative reliability and validity of a standardized eccentric strength-measurement protocol for the glenohumeral external rotators.Design: Descriptive laboratory study. Setting: Testing environment at the Department o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 31 publications
5
63
1
3
Order By: Relevance
“…The order of the tests was randomized between sides and between the procedures, in order to control the procedure for learning effects and fatigue. Each test was repeated three times with a pause in between trials of 20 s [9,11,18]. For the eccentric strength measurement, the protocol of Johansson et al [18] was used.…”
Section: Testing Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The order of the tests was randomized between sides and between the procedures, in order to control the procedure for learning effects and fatigue. Each test was repeated three times with a pause in between trials of 20 s [9,11,18]. For the eccentric strength measurement, the protocol of Johansson et al [18] was used.…”
Section: Testing Proceduresmentioning
confidence: 99%
“…Each test was repeated three times with a pause in between trials of 20 s [9,11,18]. For the eccentric strength measurement, the protocol of Johansson et al [18] was used. The subject was in a seated position, feet at shoulder width, the lower back supported against a chair, and held the elbow and shoulder at a position of 90° of abduction and 90° of external rotation (90-90) with support from the examiners hand and forearm.…”
Section: Testing Proceduresmentioning
confidence: 99%
“…A MicroFET 2 handheld dynamometer (Hoggan Health Industries, Salt Lake, UT, USA) was used to objectively measure the strength. A pilot study to test the inner reliability was not performed, since the intrarater validity and reliability when using a handheld dynamometer are well established in the litterature 2426…”
Section: Methodsmentioning
confidence: 99%
“…In terms of rotator cuff strength, an isokinetic ER/IR ratio of 66% or an isometric ER/IR ratio of 75-100% has been advised with the dominant shoulder typically 10% higher than the non-dominant side [12][13][14][15]. Johansson et al demonstrated good to excellent reliability for measuring eccentric external rotation strength using a hand-held dynamometer [36], which we have started to incorporate in our return to sport assessment.…”
Section: Criteria For Return To Sport After Shoulder Anterior Labral mentioning
confidence: 99%